The well-being implications of Urban Natures among Black Urban Dwellers in the Eastern Cape - Walsh, Lindsey Sara (Rhodes University, Faculty of Humanities, Department of Anthropology)
Throughout the world, urbanisation is at an all-time high. It is estimated that two-thirds of the global population will be living in urban centres by 2030. The highest urban growth rates are currently found in sub -Saharan Africa, however, approximately 70% of urban residents in Sub-Saharan Africa reside in informal settlements. Such processes have resulted in reduced areas of natural space and biodiversity. While the benefits of exposure to and experiences of nature to human well-being and quality of life are increasingly being acknowledged, these links are largely understood through a western lens, where nature and culture are dichotomised. The implications of this are that the types of nature(s) that are made available in urban areas are designed to provide opportunities for urban residents to only engage in recreational and relaxation activities within such places. However, among indigenous and non-westernised communities, culture is a dynamic and holistic entity, deeply rooted in the constructions of nature. Very few studies from the global south have entered this dialogue. In response, this study, conducted amongst Xhosa speaking urban residents living in two medium-sized towns, was undertaken to explore the connections and meanings they attributed to nature(s) and how their engagement in such places contributed to their sense of well-being. This study found that strong connections and meanings to nature still exist. Many of these relate to personal experiences which are given meaning through local understandings and associations which are deeply embedded within cultural practices and rituals. Engagement and or memories of such are strongly associated with a sense of well-being often only experienced in rural areas. In such contexts, well-being is also understood as a holistic concept that is underpinned by these nature-culture connections. Within an urban context, the benefits of such connections are hindered by the types of nature(s) found in these areas as well as high levels of crime and the poor management of such places.
Keywords: Apartheid -- South Africa -- Eastern Cape; Decolonization -- South Africa -- Eastern Cape; Urban Black people -- South Africa -- Eastern Cape; Quality of life -- South Africa -- Eastern Cape; Well-being -- South Africa -- Eastern Cape; Rural-urban migration -- South Africa -- Eastern Cape; Urban ecology (Sociology) -- South Africa -- Eastern Cape; Land use, Urban -- South Africa -- Eastern Cape; City and town life -- South Africa -- Eastern Cape; Sociology, Urban -- South Africa -- Eastern Cape; Nature Social aspects -- South Africa -- Eastern Cape